Poland : Reform and Restructuring of the Hard Coal Sector 1998-2006 and Future Prospects - Strongman, John (World Bank, Washington, DC, 2013)
Poland has by far the highest hard coal production of any country in the European Union and hard coal will continue to play a crucial role regarding energy security for Poland. Most importantly, hard coal can reduce both the price and supply risks for Poland associated with oil and gas imports. Poland has a number of low cost mines with good quality coal where production can be expanded so that it is feasible for coal to meet domestic demand without requiring operating support from the state budget and if the remaining restructuring of the coal mining sector is completed successfully, the sector can again become an important driver for economic development of Silesia rather than a liability. While heavy industries such as hard coal and steel will remain core industries for Silesia, they are unlikely to be sources of increased employment in future. The growth sectors for Silesia are to be found in higher technology (including coal-based technologies) and service industries. The next few years, while EU funds are available, offer Silesia a window of opportunity to develop these new sectors. It is, therefore, important that the coal industry release its surplus employees and land so that Silesia can diversify into new industries and take full advantage of EU funds while at the same time having a healthy and profitable coal industry.